Molecular Programming of Drought-Challenged Trichoderma harzianum-Bioprimed Rice (Oryza sativa L.) - Bashyal, Bishnu Maya; Parmar, Pooja; Zaidi, Najam Waris; Aggarwal, Rashmi (Frontiers in Microbiology, 2021)
Trichoderma biopriming enhances rice growth in drought stressed soils by triggering various plant metabolic pathways related to antioxidative defence, secondary metabolites, hormonal up regulation etc. In the present study, transcriptomic analysis of rice cultivar IR64 bioprimed with Trichoderma harzianum under drought stress was carried out in comparison to drought stressed samples using next gen sequencing techniques. Out of the 2506 significant (p<0.05) differentially expressed genes (DEGs), 337 (15%) were exclusively expressed in drought stressed plants, 382 (15%) in Trichoderma harzianum treated drought stressed plants and 1787 (70%) were commonly expressed. Further, comparative analysis of up-regulated and down-regulated genes under stressed conditions showed 1053 genes (42%) were upregulated and 733 genes (29%) were down regulated in T. harzianum treated drought stressed rice plants. The genes exclusively expressed in T. harzianum treated drought stressed plants were mostly photosynthetic and antioxidative such as plastocyanin, small chain of Rubisco, PSI subunit Q, PSII subunit PSBY, osmoproteins, proline-rich protein, aquaporins, stress enhanced proteins, chaperonins etc. The KEGG enrichment analysis states that the most enriched pathways were of metabolic (38%) followed by pathways involved in synthesis of secondary metabolites (25%), carbon metabolism (6%), phenyl propanoid (7%) and glutathione metabolism (3%). Some of the genes were selected for the validation using real time PCR which showed consistent expression as RNA-seq data. Further, to establish host-T. harzianum interaction, transcriptome analysis of Trichoderma was also carried out. The gene ontology (GO) analysis of T. harzianum transcriptome suggested that the annotated genes are functionally related to carbohydrate binding module, glycoside hydrolase, GMC oxidoreductase and trehalase were mainly upregulated which plays important role in establishing the mycelia colonization of rice roots and its growth. Overall, it can be concluded that the T. harzianum biopriming delays drought stress in rice cultivars by multitude of molecular programming.